Taujih al-Qiraat and Its Hermeneutical Implications in Surah Yunus - Prasetiawati, Eka (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2025)
This study examines the phenomenon of taujih al-qiraat and its hermeneutical implications in Surah Yunus, focusing on how variations among the ten canonical Qur'anic readings generate layers of linguistic and theological meaning. It identifies forty-one loci of farsh al-huruf and verifies them through four parameters: rasm (orthographic framework), dabt (diacritical precision), lughawi (lexical plausibility), and nahwi/sarfi (grammatical and morphological validity). The research adopts a descriptive-analytical method integrating classical philology with modern linguistic verification to establish a transparent and replicable model of analysis. The results show that the variants in Surah Yunus function as a structured system of semantic plurality rather than random recitational differences. Ten representative loci reveal that phonetic variations preserve the rhythm of recitation, minor semantic variations influence rhetorical emphasis, and major semantic variations shape theological interpretation. These findings confirm that taujih al-qiraat serves as both a linguistic and hermeneutical framework linking structure and meaning in the Qur'an. The study concludes that the diversity of readings in Surah Yunus reflects divine intentionality within the boundaries of the Arabic language. By aligning classical verification with contemporary analysis, it offers a verifiable model for understanding how linguistic variation contributes to the Qur'an’s interpretive depth and theological coherence.